Regional-scale land use change based on multi-scenario simulation and its impact on carbon storage: a case study of southern Jiangsu region - Zhao, Wanmei; Lei, Yanyan; Tan, Chenglin; Ma, Yuanxi; Zhang, Yuzhou (Frontiers in Sustainability, 2026)
Research on regional land-use changes and carbon storage is vital given climate change and human activities. First, the spatiotemporal characteristics of land use change and carbon storage in southern Jiangsu from 2000 to 2020 were analyzed. Using the MCCA model, future land use in southern Jiangsu for the year 2030 was simulated under various development scenarios, and the associated carbon storage was estimated. The following conclusions were drawn: (1) From 2000 to 2020, the land-use structure in the southern part of Jiangsu Province had a certain degree of stability but also underwent minor changes. Over the past 20 years, the area of cultivated land has decreased, whereas the areas of urban, rural, industrial, mining, and residential land have increased dramatically. (2) From 2000 to 2020, carbon storage in southern Jiangsu showed a trend of first decreasing and then increasing. The areas with relatively high carbon storage were primarily distributed in strips in the western part of southern Jiangsu and in the northern, central, and southern parts. Areas with relatively low carbon storage were mainly distributed in the northern part of southern Jiangsu Province, spreading outwards from multiple centers in a planar pattern. (3) The change in carbon storage of land use types in the southern Jiangsu region from 2000 to 2020 was positively correlated with changes in land use type area. (4) In 2030, the changes in land use structure and spatial distribution of land types under multiple scenarios in the southern Jiangsu region will be relatively stable. Cultivated land showed an increasing trend in the cultivated land protection scenario and a decreasing trend in the other scenarios. The research results can provide a theoretical basis for decision-makers to optimize land-use structures and rationally allocate land resources for territorial space planning in southern Jiangsu.